Identifying Gut Microbiota Associated With Colorectal Cancer Using a Zero-Inflated Lognormal Model - Ai, Dongmei; Pan, Hongfei; Li, Xiaoxin; Gao, Yingxin; Liu, Gang; Xia, Li C. (Frontiers in Microbiology, 2019)
Colorectal cancer (CRC) is the third most common cancer worldwide. Its incidence is still increasing, and the mortality rate is high, for which new therapeutic and prognostic strategies are urgently needed. It became increasingly recognized that the gut microbiota composition differs significantly between healthy people and CRC patients. Thus, identifying the difference between gut microbiota of the healthy people and CRC patients is fundamental to understand microbes’ functional roles in the development of CRC. We analyzed the microbial community structure of a CRC metagenomic dataset of 156 patients and healthy people, including its diversity, differentially abundant bacteria, and co-occurrence networks. We applied a modified zero-inflated lognormal model for estimating the relative abundance. We found the abundance of genera: Anaerostipes, Bilophila, Catenibacterium, Coprococcus, Desulfovibrio, Flavonifractor, Porphyromonas，Pseudoflavonifractor，and Weissella were significantly different between the healthy and CRC groups. We also found bacteria such as Streptococcus, Parvimonas, Collinsella, and Citrobacter were uniquely co-occurring within the CRC patients. In addition, we found that the microbial diversity of healthy people is significantly higher than that of the CRC patients and there was a significant negative correlation between gut microbiota diversity and the stage of CRC. Collectively, our results strengthened the view that individual microbes as well as the overall structure of gut microbiota were coevolving with colorectal cancer, which merits further preclinical investigations.